Polyunsaturated Fatty Acid Dietary Supplementation Induces Lipid Peroxidation in Normal Dogs - John M. Walters; Timothy B. Hackett; Gregory K. Ogilvie; Martin J. Fettman (Veterinary Medicine International)
Polyunsaturated fatty acids (PUFAs) have anti-inflammatory effects at low concentrations; however increased dietary consumption may conversely increase susceptibility to oxidation by free radicals. The objective of this study was to determine the effects of PUFAs on selective oxidative injury and inflammatory biomarkers in canine urine and serum. Dogs (n=54) consumed a diet supplemented with 0.5% conjugated linoleic acid/dry matter, 1.0% conjugated linoleic acid/dry matter, or 200 mg/kg docosahexaenoic acid/eicosapentaenoic acid for 21 days. All dogs exhibited significantly increased plasma PUFA concentrations. All dogs had significant elevations in urinary F2a isoprostane concentration, though dogs consuming a diet containing 1.0% conjugated linoleic acid/dry matter had the highest increase (P=.0052). Reduced glutathione concentrations within erythrocytes decreased significantly in all three dietary treatment groups (P=.0108). Treatment with diets containing 1.0% conjugated linoleic acid/dry matter resulted in the greatest increase in oxidant injury. Caution should be exercised when supplementing PUFAs as some types may increase oxidation.